SIKAP PEDULI SISWA SEKOLAH DASAR TERHADAP LINGKUNGAN SEKOLAH - Agustina, Diah; Dafit, Febrina (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The environment is now an interesting topic to talk about in the field of education, particularly with regard to elementary school students. Several commonly available pieces of information, particularly those demonstrating the lack of concern for the environment, are what motivated this investigation. Because of this, it is imperative that children have an attitude of environmental stewardship from an early age in compliance with governmental standards. This research aims to find out how environmentally conscious the students of Class VA SD 025 Indrasakti, Kampar Regency, are. This kind of descriptive qualitative study uses observation, interviews, and documentation as data gathering methods. This study was carried out in. The findings of the study demonstrate that the students at SD 025 Indrasakti, Kampar Regency, have an environmentally conscious attitude that aligns with the five indicators of such attitudes. These indicators include the students' prompt removal of litter from the classroom, their conservation of electricity after class, and their constant maintenance of a clean classroom. Clean up after yourself, next engage in environmental participation by emptying trash cans, and lastly take part in preserving the cleanliness of the surrounding area.